APLIKASI SIPENA BERBASIS KEARIFAN LOKAL JEPARA SEBAGAI MEDIA PEMBELAJARAN MAKNA KATA SISWA KELAS II - Siti Asiyah; Nafilatul Ilmiyyah; Mulyani Sekar Arum; Rani Setiawaty (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to develop and test the feasibility of the SIPENA Ukir Bahasa media (Application of Curious Language Meaning Based on Jepara Local Wisdom) as an innovative digital learning media to improve the ability to interpret words meaningfully in grade II elementary school students. The method used in the study is the Research and Development (R&D) method with the ADDIE model which includes the stages of design analysis, development, implementation, and evaluation. The feasibility test process by material and media experts, while practicality is obtained through teacher and student responses to the use of the application. The validation results show that this application is feasible to use with a score of 77% from media experts, and 74% from material experts. In addition, the results of the practicality test obtained from teacher and student responses are also very positive, with teacher responses of 85.8%, and 90% from students. Thus, the SIPENA application is considered interesting, easy to use, and relevant to the context of Jepara local wisdom, namely with the presence of carvings. The novelty of the SIPENA application offers innovation in the form of integrating Jepara local wisdom in learning the meaning of words based on Android. This integration makes learning more contextual and meaningful while also supporting the strengthening of character and cultural literacy in elementary school students.